Using Clumped Isotopes to Reconstruct the Maximum Burial Temperature: A Case Study in the Sichuan Basin - Li, Pingping; Duan, Jinbao; Cheng, Zhongzhen; Zou, Huayao (Frontiers in Earth Science, 2021)
For strata that have experienced continual burial in the early stage and uplift in the late stage, the present-day temperature is lower than the maximum burial temperature (MBT), which is a key parameter for studying the hydrocarbon generation history of source rocks in petroliferous basins. In this paper, a new method for reconstructing the MBT is proposed based on the solid-state reordering model of carbonate clumped isotopes (Δ47). The MBT reconstructed using the Δ47 was compared with the MBT constrained using the traditional Easy%Ro model. The clumped isotope temperature (TΔ47) of the Permian micritic limestone from the Xibeixiang outcrop (about 62°C) is much higher than its initial formation temperature (20–25°C), suggesting that the limestone experienced partial solid-state reordering during the late burial process. The MBT of the calcite obtained from the solid-state reordering model is 139–147°C, which is quite similar to the MBT determined using the Easy%Ro model (139.5–147.5°C). TΔ47 of the Permian and Triassic limestone and calcite cements in the Puguang gas field are 150–180°C, while TΔ47 of the micritic dolostone is about 70°C, suggesting that the Δ47 of the limestone and calcite cements experienced complete solid-state reordering and the dolostone only experienced partial solid-state reordering. The MBT of the dolomite determined using the solid-state reordering model is 200–220°C, which is also similar to the MBT determined using the Easy%Ro model (202–227°C). Therefore, the case studies from the Sichuan Basin suggest that Δ47 can be used to reconstruct the MBT of ancient carbonate strata lacking vitrinite and detrital zircon data. However, different types of carbonate samples should be used to reconstruct the MBT for strata that have experienced different temperature histories. Micritic limestone and very finely crystallized dolostone can be used to reconstruct the MBT of strata that have experienced MBTs of < 150–200°C and > 200 –250°C, respectively.